Measurements of confined jet - Tan, Jie Lun (2014)
The target of the confined jet will create a flip flop effect of the flow when the jet hitting it. The frequency of the flip flop will vary with the flow velocity and thus the confined jet can be used as a flow meter once the relationship established. The scope of the project including (1)using the hot-wire to measure the mean and root measure square of the velocity in x direction, (2) the effect of the distance of the target from the jet on the flip flop frequency, and (3) the size of the target on the effect of the flip flop frequency.